Writing As A Skill: Problems Identified And Pedagogical Remedies - Nazim, Mohd (Advances in Social Sciences Research Journal, 2018)
This study identifies and discusses some common writing problems among Saudi students. The study upholds that pedagogically, writing as a skill and not as an activity has to be taught. The study argues that most of these writing problems arise from pedagogical reasons and a fresh look is needed to find out the pedagogical solutions of common writing problems i.e. punctuation and capitalization, grammatical structure, and language use. To a greater extent, these problems are not limited only to the Preparatory Year (Najran University), involved in the study, but apply also to other teaching and learning levels as well. Thus, the study advocates that writing problems can be minimized if the students are taught writing as a skill by professional language practitioners in an environment where students not only engage themselves in writing activities but also enjoy and develop writing as a skill.